A Mealybug Phenacoccus multicerarii Granara de Willink (Hemiptera: Pseudococcidae) - Ian Stocks (EDIS, 2013)
Florida Department of Agriculture and Consumer Services, Division of Plant Industry inspector Lisa Hassell collected the mealybug Phenacoccus multicerarii, a new continental record, from a retail nursery in Fernandina Beach (Nassau County, on 15 June 2011). On a return visit to the store, the mealybug was observed in high numbers on numerous host plants. Three days later, an additional find was made at a nursery in Apopka that had exchanged plant material with the nursery in Jacksonville. No further infestations were reported until October 2012, when a heavy infestation was discovered on a residential planting of coleus in Cooper City (Broward County). This mealybug was described in 2007 from a sample collected in Caracas, Venezuela, in 1949 from an unknown host (Granara de Willink and Szumik 2007). This 2-page fact sheet was written by Ian Stocks, and published by the UF Department of Entomology and Nematology, April 2013.